Redescription of Stilobezzia (Stilobezzia) albicoxa Lane & Forattini, 1956 with new synonymy (Diptera: Ceratopogonidae) - Da Silva, Irene Marques; Ferreira-Keppler, Ruth L.; Hamada, Neusa; Cazorla, Carla G. (Zootaxa, 2020)
Stilobezzia Kieffer, 1911 is a diverse genus of predaceous Ceratopogonidae (Ceratopogoninae: Ceratopogonini) with 349 species recognized worldwide (Borkent & Dominiak 2020). The genus has four subgenera, three occurs in Brazil, where Stilobezzia s. str. is the most speciose, with 23 species registered (Santarém & Felippe-Bauer 2019).